2022
DOI: 10.3390/polym14071294
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable and Sensitive Multimodal Tactile Sensor Based on Conductive Rubber Composites to Monitor Pressure and Temperature

Abstract: Stretchable and flexible tactile sensors have been extensively investigated for a variety of applications due to their outstanding sensitivity, flexibility, and biocompatibility compared with conventional tactile sensors. However, implementing stretchable multimodal sensors with high performance is still a challenge. In this study, a stretchable multimodal tactile sensor based on conductive rubber composites was fabricated. Because of the pressure-sensitive and temperature-sensitive effects of the conductive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…With the development of science and technology, the demand for integration and miniaturization is increasing, so multimodal sensors have emerged Table summarizes the performance parameters of the most recent multimodal sensors. ,,,,,,,,, Multimodal biochemical sensors are partially described in Tables –, so only some of the multimodal biochemical sensors are listed in Table . The table shows that multimodal sensors are integrated with two or more sensors on the same substrate to achieve multifunctional measurements.…”
Section: Multimodal Physiological and Biochemical Sensorsmentioning
confidence: 99%
“…With the development of science and technology, the demand for integration and miniaturization is increasing, so multimodal sensors have emerged Table summarizes the performance parameters of the most recent multimodal sensors. ,,,,,,,,, Multimodal biochemical sensors are partially described in Tables –, so only some of the multimodal biochemical sensors are listed in Table . The table shows that multimodal sensors are integrated with two or more sensors on the same substrate to achieve multifunctional measurements.…”
Section: Multimodal Physiological and Biochemical Sensorsmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS), as a kind of silicone elastomer that has proven to be a promising substrate due to its great stretchability, high thermal stability, chemical stability, simple processing, low price, etc. [ 44 , 45 , 46 ]. Due to its thinness, breathability, and excellent biocompatibility, it can be directly attached to human skin without causing allergic reactions or used as a flexible tissue-engineering material implanted in the body [ 47 , 48 , 49 ].…”
Section: Polymersmentioning
confidence: 99%
“…A flexible capacitive tactile sensor was proposed for multi-directional force-sensing [ 71 ]. The sensor was based on a dielectric layer of a carbon black/PDMS composite and upper and lower electrodes of carbon nanotubes (CNTs)/PDMS composite layer.…”
Section: Conducting Polymers As a Charge Transfer Base For Tactile Se...mentioning
confidence: 99%
“…This was explained according to the percolation theory. The prototype with the carbon black/PDMS composite dielectric layer was fabricated and characterized, and it was concluded that the resolution of the carbon sensor could reach 0.1 N within 50 N in a normal direction, and 0.2 N in 0–10 N in a tangential direction, with good stability [ 71 ].…”
Section: Conducting Polymers As a Charge Transfer Base For Tactile Se...mentioning
confidence: 99%
See 1 more Smart Citation